Vitamin C for your smartphone : the SKIMS approach for cooperativeand lightweight security at mobiles - Matthias Wählisch and Sebastian Trapp and Jochen Schiller and Benjamin Jochheim and Theodor Nolte and Thomas C. Schmidt and Osman Ugus and Dirk Westhoff and Martin Kutscher and Matthias Küster and Christian Keil and Jochen Schönfelder (ACM SIGCOMM computer communication review, 2012)
Smartphones are popular attack targets, but usually too weak in applying common protection concepts. SKIMS designs and implements a cooperative, cross-layer security system for mobile devices. Detection mechanisms as well as a proactive and reactive defense of attacks are core components of this project. In this demo, we show a comprehensive proof-of-concept of our approaches, which include entropy-based malware detection, a mobile honeypot, and spontaneous, socio-inspired trust establishment.
Keywords: Mobile security; malware detection; mobile honeypot; ad hoc trust